Fast Dynamic in vivo Monitoring of Erk Activity at Single Cell Resolution in DREKA Zebrafish - Mayr, Vanessa; Sturtzel, Caterina; Stadler, Manuela; Grissenberger, Sarah; Distel, Martin (Frontiers in Cell and Developmental Biology, 2018)
Precise regulation of signaling pathways in single cells underlies tissue development, maintenance and repair in multicellular organisms, but our ability to monitor signaling dynamics in living vertebrates is currently limited. We implemented kinase translocation reporter technology to create DREKA (“dynamic reporter of Erk activity”) zebrafish, which allow one to observe Erk activity in vivo at single cell level with high temporal resolution. DREKA zebrafish faithfully reported Erk activity after muscle cell wounding and revealed the kinetics of small compound uptake. Our results promise that kinase translocation reporters can be adapted for further applications in developmental biology, disease modeling and in vivo pharmacology in zebrafish.